Employing interdisciplinary approaches to generate public health solutions for emerging vector-borne diseases - Cagle, Shelby Morgan, author; Kelp, Nicole, advisor; Kading, Rebekah C., advisor; Mayo, Christie, committee member; Lynn, Stacy, committee member (Colorado State University. Libraries, 2025)
WHO attributes 700,000 deaths and 17% of all infectious diseases each year to vector-borne diseases (VBD). Communities who live in certain geographic regions or within lower socioeconomic sectors are disproportionately at risk for VBD, but the threat is widespread as global climate changes, travel increases, and international trade facilitates the spread of VBD. Ecological factors, such as temperature, can alter vector capacity and disease kinetics; whereas social factors, such as individual perceptions and behaviors, could limit or exacerbate risk for VBD. Emerging and re-emerging diseases are of concern for both human and animal health as zoonotic diseases are the most likely to spread. Therefore, an integrative approach that considers host-vector-pathogen interactions, environmental conditions, socioecological dynamics, public health communication, and other sectors is necessary to reduce the global burden of emerging vector-borne diseases (EVBD). In this project, three science communication studies were conducted to train early career scientists in evidence-based approaches for health misinformation correction, to explore public perceptions about emerging infectious disease research, and to evaluate public health messaging strategies about West Nile virus. From these studies, critical insights were gained on how to communicate about EVBD with diverse audiences and improve public health outcomes. This is complemented by laboratory studies that evaluate the risk of Rift Valley fever virus in light of ecological changes, namely temperature shifts. Furthermore, data are presented that support that RVFV transmits vertically in two mosquito vectors of interest, Aedes aegypti and Culex tarsalis. When taken together, this research exemplifies the need for interdisciplinary research to generate evidence-based and sustainable solutions.